Partial and Whole Breast Radiation Have Similar Outcomes in Early BC - Cunningham, Muriel (MD Conference Express, 2014)
A single-center randomized study of 520 patients with early breast cancer compared accelerated partial breast irradiation using intensity modulated radiotherapy to whole breast irradiation. No differences were seen in the 5-year rate ipsilateral breast tumor recurrence rate and significantly less skin toxicity was observed with partial breast irradiation.